Implementation of a mobile application: sales optimization in a Peruvian company - Ligarda Motta, Joel Ricardo (2022)
At present, companies in the retail sector seek to expand their markets in various ways, always seeking to sell their products to more and more customers, which is why they have opted for e-commerce. Selling and buying online is today essential in every company. Moreover, most businesses opt for a mobile application because most purchases are made from smartphones. Therefore, this application seeks to help customer loyalty by providing users with an interface that motivates them to buy. The progress of the application was based on five sprints which developed the user stories, prototypes were presented, which were used for surveys in which the dimensions were included, collecting important statistical data for the development and improvement of the application. In this research work, an application was designed using the Scrum methodology to carry out sales processes using mobile devices. Additionally, this work shows, as a result, optimal Technological prototyping in which the personalization of the sales process, attractive design, recommendations, and offers are rescued, and all of this seeks to retain users to convert them into clients. In the future, the use of augmented reality is contemplated, big data and the use of AI.